The effects of material property assumptions on predicted meltpool shape for laser powder bed fusion based additive manufacturing. (12th July 2016) - Teng, Chong; Ashby, Kathryn; Phan, Nam; Pal, Deepankar; Stucker, Brent
Abstract: The objective of this study was to provide guidance on material specifications for powders used in laser powder bed fusion based additive manufacturing (AM) processes. The methodology was to investigate how different material property assumptions in a simulation affect meltpool prediction and by corrolary how different material properties affect meltpool formation in AM processes. The sensitvity of meltpool variations to each material property can be used as a guide to help drive future research and to help prioritize material specifications in requirements documents. By identifying which material properties have the greatest affect on outcomes, metrology can be tailored to focus on those properties which matter most; thus reducing costs by eliminating unnecessary testing and property charaterizations. Futhermore, this sensitivity study provides insight into which properties require more accurate measurements, thus motivating development of new metrology methods to measure those properties accurately.